Kualiti Kehidupan Bekerja Dan Hubungannya Dengan Komitmen Terhadap Organisasi - Noraini, Abdullah Sani (2000)
Parallel to the widespread of information technology today, the workload and responsibilities of the teachers are becoming very demanding and challenging. Hence, there are reports on the declining of their quality of work and commitment towards their organization that resulted in absenteeism and early retirement. This study aims at identifying the relationship between quality of work life and commitment towards the organization among the secondary school teachers in the Kota Setar district in Kedah Darul Aman. In measuring the level of commitment towards the organization among the teachers, some improvements were made to the Organizational Commitment Questionnaire (OCQ) by Mowday, et. al. (1975) so as to fit the selected respondents. Items on quality of work life were designed based on the eight criteria suggested by Walton (1973). This research also studies the differences in demographic factors such as sex, age and tenure on commitment towards the organization. A pilot study was conducted to test the reliability and validity of the instrument. For the study, the administrators of the respective fifteen secondary schools in the Kota Setar district randomly selected three hundred and forty teachers. The questionnaire used consists of forty-three items, which is then divided into three parts. The statistical analyses used in the study are t-Test, Oneway ANOVA, Pearson Correlation and Multiple Regression. The results of the study indicate that there was a significant relationship between quality of work life and commitment towards the organization. The study also found that the eighth criterion of the independent variable is the most influential factor on commitment towards the organization. The result of the t-Test and One-way ANOVA portrays that the differences in the demographic factors were not significant. The correlation test shows that six out of the eight criteria of quality of work life are positively significant to commitment towards the organization.